MEMBANGUN INKLUSIFITAS BERAGAMA MELALUI LITERASI DIGITAL DI MA’HAD ALY - Dakir, Dakir; Zubaidi, Ahmad; Hasanah, Nur Silfiatun (JURNAL ISLAM NUSANTARA, 2020)
The research aims to analyze and understand the efforts made by Ma'had Aly Nurul Jadid Paiton Probolinggo in building religious inclusiveness through digital literacy for the academic community. This study uses a qualitative approach to the type of phenomenology, in which the researcher tries to understand the phenomena that occur and develop. Data collection techniques are carried out through participant observation, interviews and documentation. The data analysis was carried out through the stages of presenting data, reducing data and drawing conclusions. The results showed that digital literacy carried out by Ma'had Aly Nurul Jadid Paiton Probolinggo in building religious inclusiveness was carried out through the utilization of digital books, scientific halaqoh, online recitation and virtual knowledge sharing.Â